Design for a nanoscale single-photon spin splitter for modes with orbital angular momentum - Li, G. (2018)
We propose using the effective spin-orbit coupling of light in Bragg-modulated cylindrical waveguides for the efficient separation of spin-up and spin-down photons emitted by a single photon emitter. Because of the spin and directional dependence of photonic stop bands in the waveguides, spin-up (-down) photon propagation in the negative (positive) direction along the waveguide axis is blocked while the same photon freely propagates in the opposite direction. Frequency shifts of photonic band structures induced by the spin-orbit coupling are verified by finite-difference time-domain numerical simulations.